Mathematical Numeracy Analysis Based on Learning Style in PBL With Differentiation E-Module - Triyono Triyono; Masrukan Masrukan; Bambang Eko Susilo (Universitas Suryakancana, 2026)
This study aims to examine the effectiveness of Problem-Based Learning assisted by differentiated e‑modules in enhancing junior high school students’ mathematical numeracy and to analyse numeracy development from the perspective of students’ learning styles. A mixed methods approach with a sequential explanatory design was employed. Quantitative data were collected using a quasi‑experimental pretest–posttest control group design, followed by qualitative data obtained through classroom observations and semi‑structured interviews. Participants consisted of Grade VIII students from a public junior high school in Indonesia. The quantitative results show that the experimental group achieved a higher increase in mathematical numeracy scores (from M = 58.75 to M = 78.63) compared to the control group (from M = 59.21 to M = 69.03). An independent sample t‑test revealed a statistically significant difference in posttest scores between the two groups (p = 0.001). In addition, learning mastery in the experimental group (84.37%) exceeded that of the control group (65.62%). Qualitative findings indicate that differentiated e‑modules effectively supported engagement and understanding across visual, auditory, and kinesthetic learning styles. This study demonstrates that the integration of PBL, learning‑style‑based differentiation, and e‑module assistance produces a cumulative effect on students’ mathematical numeracy. The findings contribute empirical evidence for designing inclusive, problem‑oriented, and digitally supported mathematics instruction.